Applying theoretical components to the implementation of health-promoting schools. (March 2015) - McIsaac, Jessie-Lee; Storey, Kate; Veugelers, Paul J; Kirk, Sara FL
Objective: Health-promoting schools (HPS) constitute an internationally recognised approach that connects health and education in a planned, integrated and holistic way. There is considerable variability, however, in how HPS is implemented and recent research has attempted to clarify the key functions of implementation. A provincial HPS strategy in Nova Scotia (NS) (Canada) provided a unique research opportunity to examine implementation related to emerging theory. The purpose of this exploratory study was to describe a provincial case study of HPS implementation using theoretical components identified in the literature. Design: Collective case study approach using qualitative research methods. Setting: The study was situated within a larger province-wide school-based research project examining the relationships between health, nutrition, physical activity, mental health and school performance of children in NS. As a follow-up to the provincial study, nine schools ( n = 9) that varied in their HPS implementation strategies and characteristics (i.e. size and region) were invited to take part as case study schools. Method: Data collection included observations, interviews and documents from nine schools ( n = 9). Data were analysed for emerging themes and using the a priori theoretical components. Results: The results revealed that schools assembled into three sequential categories based on the functioning of theoretical components. Higher level visioning and school-level leadership were critical in sustaining the adoption and implementation of HPS across schools and appeared to enable and integrate organisational processes, such as distributed leadership and a collaborative school culture, to enhance HPS implementation at school level. Conclusion: This study confirmed other reports that it is imperative to integrate HPS work with educational values so as to enable partnerships in both the health and education sectors, thereby promoting both health and prosperity among students.